Development of a Centralized Controlling System with Real-time Monitoring: Internet of Things, CCTV, Public Address, and FDAS: 4-Systems in One Dashboard System using Raspberry Pi - Bernabe Jr., Reynaldo Q.; Junio, Oliver M. (International Journal of Computing Sciences Research, 2024)
Purpose – The main purpose of this study is to develop an innovative approach for real-time control and monitoring of the facilities of an institution and it aims to minimize further casualties in case of untoward incidents and minimize the electrical cost. Method – The study utilized descriptive methods by identifying the currently installed systems through observation, interviews, and surveys. The report proposed a novel strategy for centralized control and real-time monitoring for the institution using the developmental research approach. Results – The study aimed to modernize a management system of facilities in an institution. The focus was to integrate all four (4) different systems into one dashboard. Findings showed the effectiveness of this innovative system, particularly at controlling and real-time monitoring using the Internet of Things, CCTV, Public address system, and FDAS; receiving a Highly Efficient rating and easy to manage compared to the traditional separate systems. Conclusion – This research was able to create a working prototype that can control and monitor the facilities. This has achieved great and promising results in terms of usability gaining the highest rating. Recommendations – Though it has a Highly Efficient rating, maintenance is still recommended to ensure the successful implementation of this innovation. Future research may be performed to consider other aspects of the management system and/or different study locations, as the aforementioned system is new and still unknown in other areas. Research Implications – Looking at the great significance of this system, this explicit focus can be manifested in how the administration should have a chance to upgrade the traditional system into this one dashboard that covers other systems. Practical Implications – The latest trend in any workforce is the implementation of system innovations. Innovative systems facilitate commerce by organizing tasks, manageable environments, and systematizing procedures.